PERMEABILIZATION, CELL WALL ULTRASTRUCTURE, AND GERMINATION OF BASIDIOSPORES OF THE ECTOMYCORRHIZAL FUNGUS Pisolithus microcarpus TREATED WITH DIFFERENT COMMERCIAL BRANDS OF BLEACH - Silvério, Merielle Angélica Martines [UNESP]; Nascimento, Jaqueline Maria Do; Serrão, José Eduardo; Tótola, Marcos Rogério; Costa, Maurício Dutra (Sociedade de Investigações Florestais, 2021)
Basidiospores of the ectomycorrhizal fungus Pisolithus microcarpus have an impermeable cell wall, a characteristic that is possibly related to the low germination percentages of these propagules, which makes it difficult to obtain monokaryons and use these spores in inoculants. The objective of this study was to evaluate the effect of different concentrations of commercial bleach on the permeabilization of P. microcarpus basidiospores and to analyze the alterations caused in the cell wall ultrastructure and the viability and germination capacity of these propagules. Fungal basidiospores were collected in eucalyptus plantations and permeabilized using different bleach concentrations and exposure times. The basidiospores were then analyzed by scanning and transmission electron microscopy. The percentage of permeabilized basidiospores varied with the commercial brand, bleach concentration, and exposure time. Basidiospores of different basidiocarps differed in susceptibility to permeabilization treatment with bleach. Changes in the ultrastructure of permeabilized basidiospores were observed at bleach concentrations of 15 and 50 % for an exposure time of 40 s, with surface changes and loss of the spicules of the outermost layer of the wall. After permeabilization with 5 % bleach for 40 s, 80 % of the permeabilized spores were viable, resulting in the production of fungal colonies after 15 days of incubation of these propagules in the presence of Corymbia citriodora. However, the germination percentage obtained, 0.001 %, was similar to that of non-permeabilized basidiospores, indicating that other factors, besides cell wall permeability, are determinant for the germination process.

Basidiósporos do fungo ectomicorrízico Pisolithus microcarpus apresentam parede celular impermeável, característica possivelmente relacionada às baixas porcentagens de germinação desses propágulos, o que dificulta a obtenção de monocários e a utilização desses esporos em inoculantes. O objetivo deste estudo foi avaliar o efeito de diferentes concentrações de água sanitária comercial na permeabilização dos basidiósporos de P. microcarpus e analisar as alterações causadas na ultraestrutura da parede celular, na viabilidade e na capacidade germinativa desses propágulos. Basidiósporos fúngicos foram coletados em plantações de eucalipto e permeabilizados utilizando-se diferentes concentrações de água sanitária e tempos de exposição. Os basidiósporos foram então analisados por microscopia eletrônica de varredura e de transmissão. A porcentagem de basidiósporos permeabilizados variou com a marca comercial, concentração de água sanitária e o tempo de exposição. Basidiósporos de diferentes basidiocarpos diferiram na suscetibilidade ao tratamento de permeabilização com água sanitária. Alterações da ultraestrutura dos basidiósporos permeabilizados foram observadas nas concentrações de 15 e 50 % de água sanitária pelo tempo de exposição de 40 s, com mudanças de superfície e perda das espículas da camada mais externa da parede. Após a permeabilização com água sanitária a 5 % por 40 s, 80 % dos esporos permeabilizados encontravam-se viáveis, resultando na produção de colônias fúngicas após 15 dias de incubação desses propágulos na presença de Corymbia citriodora. No entanto, a porcentagem de germinação obtida: 0,001%, foi semelhante à de basidiósporos não-permeabilizados, indicando que outros fatores, além da permeabilidade da parede celular, são determinantes para o processo de germinação.
PERMEABILIZAÇÃO, ULTRAESTRUTURA DA PAREDE CELULAR E GERMINAÇÃO DE BASIDIÓSPOROS DO FUNGO EcTOMICORRÍZICO Pisolithus microcarpus TRATADOS COM DIFERENTES MARCAS COMERCIAIS DE ÁGUA SANITÁRIA
Keywords: Ectomycorrhiza; Inoculant; Eucalyptus; Ectomicorriza; Inoculante; Eucalyptus